Type and duration of water stress influence host selection and colonization by exotic ambrosia beetles (Coleoptera: Curculionidae) - Ranger, Christopher M.; Parajuli, Madhav; Gresham, Sean; Barnett, Jenny; Villani, Sara; Walgenbach, James; Baysal-Gurel, Fulya; Owen, James S.; Reding, Michael E. (Frontiers in Insect Science, 2023)
This is a provisional file, not the final typeset article Fungus-farming ambrosia beetles in the tribe Xyleborini tunnel into plants and trees to establish chambers for cultivating their nutritional fungal mutualists and rearing offspring. Some xyleborine ambrosia beetles preferentially infest and perform better in living but weakened trees. Flood stress predisposes horticultural tree crops to infestation, but the impact of drought stress has not been well studied. Our objectives were to compare the effects of flood stress vs. drought stress, and to assess the duration of flooding, on host selection and colonization by xyleborine ambrosia beetles.Container-grown Cornus florida L. trees were flood stressed using a pot-in-pot system to submerge the roots in water while drought stressed conditions were imposed by withholding irrigation and precipitation. When experimental trees were held under field conditions for 14 days, 7.5× more ambrosia beetles landed on stems of the flood stressed vs. drought stressed trees. During two additional experiments over 14 and 22 days, ambrosia beetles tunneled into the flood stressed trees but not the drought stressed or standard irrigation trees. By simultaneously deploying trees that were flood stressed for varying lengths of time, more tunnel entrances, xyleborine adults and offspring were recovered from trees that were flooded for 1-16 days and 7-22 days compared to trees that were flooded for 14-29 days and 28-43 days. These results indicate that acute and severe drought stress does not predispose C. florida to infestation, but flood stress and the duration of flooding influence ambrosia beetle host selection and colonization. Understanding the role of host quality on ambrosia beetle preference behavior will assist with predicting the risk of horticultural tree crops to infestation by these opportunistic insects.